2021
DOI: 10.1002/jbt.22929
|View full text |Cite
|
Sign up to set email alerts
|

Cefepime and diclofenac sodium combined treatment‐potentiated multiple organ injury: Role of oxidative damage and disrupted lipid metabolism

Abstract: Concurrent exposure to antimicrobial and nonsteroidal anti-inflammatory drugs (NSAIDs) is usually inevitable in most infections and postsurgery. Consequently, the present study was designed to assess the intertwining impact of coadministration of cefepime (CP, a wide spectrum antibiotic) and diclofenac sodium (DF, an NSAID) on rat's liver, kidney, and testes. Rats received saline, CP (180 mg/kg/day, IM), DF (10 mg/kg/day, IM), or a combination of CP and DF. After 14 days, CP or DF induced tissue damage express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…Surprisingly, according to the current histological study, the proximal tubules were the most affected areas of the kidneys following Cd intoxication. These findings are consistent with our prior research, which indicates the vulnerability of the cortical region to oxidative degradation caused by different insults such as gentamicin ( Abdeen et al, 2021 ), cefepime ( Aboubakr et al, 2021a ), and aflatoxins B 1 ( Abdel-Daim et al, 2021 ). Therefore, it is strongly assumed that mitochondria constitutes a potential subcellular target for Cd ( Gobe and Crane, 2010 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Surprisingly, according to the current histological study, the proximal tubules were the most affected areas of the kidneys following Cd intoxication. These findings are consistent with our prior research, which indicates the vulnerability of the cortical region to oxidative degradation caused by different insults such as gentamicin ( Abdeen et al, 2021 ), cefepime ( Aboubakr et al, 2021a ), and aflatoxins B 1 ( Abdel-Daim et al, 2021 ). Therefore, it is strongly assumed that mitochondria constitutes a potential subcellular target for Cd ( Gobe and Crane, 2010 ).…”
Section: Discussionsupporting
confidence: 93%
“…Oxidative distress is renowned for being initiated when the produced ROS, such as superoxide anions (O 2 •− ), hydroxyl radicals (OH • ), and hydrogen peroxide (H 2 O 2 ), overrides the endogenous antioxidant's capacity ( Abdeen et al, 2019 ). Thereafter, tissue injury is elicited via provoking a cascade of complex mechanisms, such as the enhancement of LPO, protein misfolding, mitochondrial perturbation, depleted ATP production, and DNA damage ( Abdel Moneim et al, 2014 ; Aboubakr et al, 2021a ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current findings are in complete agreement with our previous experiments. The tissue injury generated by oxidative stress-inducing agents was promoted when given in combination such as cadmium with piroxicam [41] and cefepime with diclofenac sodium [49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adverse drug–drug interactions of diclofenac, when tested in combination with other drugs such as ACE inhibitors, antimicrobial agents, anticoagulants, and cyclosporine, have also been reported. A recently concluded study in mice found the concomitant use of cefepime and diclofenac led to multiple organ failure [ 148 ]. The potential of diclofenac as an antimicrobial agent, anticonvulsant, amyloid inhibitor, and anticancer agent has been proposed and tested.…”
Section: Discussionmentioning
confidence: 99%